The Relationship between Knowledge with Attitudes of College Students towards the HPV Vaccine - Seo, Jordhy Kevin Christoper; Neri, Heliana; Maturan, Ameylia Martesi; Cathryne, Joice; Debby, Chryest (Universitas Prima Indonesia, 2024)
Cervical cancer is the second-deadliest disease in the world for women after breast cancer. Many women who have cervical cancer, when found, have already entered the final stage, making it difficult to cure. Cervical cancer can prevented by using the human papilloma vaccine, but many women do not vaccinate because they lack knowledge and information. Based on the results of interviews with 20 female students, 18 did not know about the human papilloma vaccine, and 4 had a history of cervical cancer in their family. This study aimed to determine the relationship between the knowledge and attitude of female students towards the human papillomavirus vaccine at faculty teachers college Pelita Harapan University. This research method uses a cross-sectional approach with 101 students as a sample, and the sampling technique used is purposive sampling. The results of data analysis using the Chi-Square test showed a p-value of 0.002 (p<0.005). In conclusion, there is a relationship between the knowledge and attitude of female students toward the human papillomavirus vaccine. Further research will research factors related to attitudes towards the human papillomavirus vaccine other than knowledge.